Warunkowe zawieszenie wykonania kary w perspektywie zmian wprowadzonych Ustawą z dnia 20 lutego 2015 r. o zmianie ustawy — Kodeks karny oraz niektórych innych ustaw - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Suspended sentence in Polish criminal law has afairly long traditionThis institution has found its place in the Penal Code of 1932 Art. 61–64, the Penal Code of 1969 Art. 73–79, as well as — in asignificantly expanded form — in the Penal Code of 1997.Suspended sentence of imprisonment has in the course of the last several years become the main means of penal policy in our country, leading to awhole range of problems. The aim of the paper is to analyze the very far-reaching modification of this institution which took place in connection with the adoption of the Act of 20 February 2015.
Keywords: warunkowe zawieszenie wykonania kary; nadzór; obowiązki w okresie próbnym; kara dodatkowa